Brønsted acid sites based on penta-coordinated aluminum species - Wang, Zichun; Jiang, Yijiao; Lafon, Olivier; Trébosc, Julien; Duk Kim, Kyung; Stampfl, Catherine; Baiker, Alfons; Amoureux, Jean-Paul; Huang, Jun (Nature communications, 2016)
Zeolites and amorphous silica-alumina (ASA), which both provide Brønsted acid sites (BASs), are the most extensively used solid acid catalysts in the chemical industry. It is widely believed that BASs consist only of tetra-coordinated aluminum sites (Al IV ) with bridging OH groups in zeolites or nearby silanols on ASA surfaces. Here we report the direct observation in ASA of a new type of BAS based on penta-coordinated aluminum species (Al V ) by 27 Al-{ 1 H} dipolar-mediated correlation two-dimensional NMR experiments at high magnetic field under magic-angle spinning. Both BAS-Al IV and -Al V show a similar acidity to protonate probe molecular ammonia. The quantitative evaluation of 1 H and 27 Al sites demonstrates that BAS-Al V co-exists with BAS-Al IV rather than replaces it, which opens new avenues for strongly enhancing the acidity of these popular solid acids. Until now, it has been believed that Brønsted acid sites in amorphous silica-alumina are formed from only tetra-coordinated (Al IV ) sites. Here, the authors use 27 Al-{ 1 H} correlation NMR experiments to identify a new Al V -based Brønsted acid site, with implications for increasing the acidity of solid acid catalysts.